Exposure to ozone gases in pulp mills and the onset of rhinitis - Hoffman, Christopher D; Henneberger, Paul K; Olin, Anna-Carin; Mehta, Amar; Torén, Kjell (Scandinavian Journal of Work, Environment & Health, 2004)
' ' OBJECTIVE ': 'Rhinitis is a common upper respiratory disease influenced by both genetic and environmental factors. It is also accepted that allergic rhinitis may precede asthma, a disease with more serious consequences. The purpose of this study was to determine whether the risk of noninfectious rhinitis is increased after accidental gassings of ozone among bleachery workers in two pulp mills. ' ' METHODS ': 'Bleachery workers (N=120) from two Swedish pulp mills using ozone as their bleaching agent were compared with control workers (N=80) not exposed to ozone in two adjacent paper mills. All of the participants were mailed a respiratory questionnaire that included items about asthma, noninfectious rhinitis, self-reported gassings, and smoking. Hazard ratios (HR) were calculated with proportional hazards regression models. ' ' RESULTS ': 'The bleachery workers who reported gassings from ozone were found to be at increased risk of noninfectious rhinitis [HR 3.4, 95% confidence interval (95% CI) 1.3–8.7] when compared with control workers. Bleachery workers without self-reported ozone gassings were not at increased risk (HR 0.9, 95% CI 0.3–2.4). ' ' CONCLUSION ': 'Acute exposure to high levels of ozone increases the risk of noninfectious rhinitis. This finding supports the view that peak exposures to irritants should be prevented in pulp mills.
Keywords: bleachery worker; exposure; ozone; ozone gas; pulp mill; rhinitis